The Development of Student Textbooks with Problem-Based Learning Approach in Higher Education: is Effective? - Kurniawan, Riza Yonisa; Prakoso, Albrian Fiky; Soesatyo, Yoyok; Pechinthorn, Komm (IKIP Widya Darma Surabaya, 2025)
Objective: This study aims to investigate the feasibility, practicality, and effectiveness of Statistics textbooks in Economic Education based on problem-based learning. Method: This research used a development research model. Model development in teaching materials contextual-based and problem-solving used model 4-P is adapted from the development model of the 4-D by Thiagarajan. Results: Recently, we revealed a novel acquisition of statistics textbooks at a very feasible level. A very practical level of practicality was obtained by the perception of 87% of students and 80% of lecturers, and then the effectiveness of the category is very effective with 80% classical completeness. Novelty: Therefore, this statistics textbook for economics education attempts to integrate a project-based learning model, from pre-research to publication, to provide students with a comprehensive research experience. This is based on validation results from various aspects, including material coverage, updates, and productivity insights. Based on the material coverage, there is a good match between the available core competencies and students' needs for the material.